2016
DOI: 10.1111/itor.12354
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of blood sample collection with timing and quality constraints

Abstract: We focus on planning transportation operations within a blood sample supply chain, which comprises clinics and a laboratory. Specifically, the main goal of this study is to obtain the optimal number of vehicles to be deployed and the scheduling of the pickup process. First, we formulate a mixed-integer programming (MIP) problem. Next, we develop a heuristic scheme composed of two heuristic algorithms and numerical search, and a new genetic algorithm. In an extensive numerical study, based on the data from a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The model proposed by Coelho et al [33] was considered as the base model and extended by incorporating product age, FF policy, and supplying planning decisions. To do so, we first investigated the most relevant models presented in previous works, including Qiu et al [34], Elalouf et al [35], and Hosseinifard and Abbasi [36]. Choosing these models was because td with optimizing integrated production and distribution decisions making similar or neighboring assumptions and objectives.…”
Section: Proposed Mathematical Modelmentioning
confidence: 99%
“…The model proposed by Coelho et al [33] was considered as the base model and extended by incorporating product age, FF policy, and supplying planning decisions. To do so, we first investigated the most relevant models presented in previous works, including Qiu et al [34], Elalouf et al [35], and Hosseinifard and Abbasi [36]. Choosing these models was because td with optimizing integrated production and distribution decisions making similar or neighboring assumptions and objectives.…”
Section: Proposed Mathematical Modelmentioning
confidence: 99%
“…Ensafian et al ( 2017 ), Ensafian and Yaghoubi ( 2017 ), Osorio et al ( 2017 ), Hosseinifard and Abbasi ( 2018 ), Clay et al ( 2018 ), Hosseinifard et al ( 2020 ) can be shown as recent examples. In addition, Ghandforoush and Sen ( 2010 ), Şahinyazan et al ( 2015 ), Blake et al ( 2015 ), Gunpinar and Centeno ( 2016 ), Elalouf et al ( 2018 ) focus on the logistics of blood products in the supply chain. The status of the blood supply chain network design and optimization after any disaster and emergency situations is also a sub-area.…”
Section: Literature Surveymentioning
confidence: 99%
“…In general, a BSC network is a four-tier supply chain that includes blood collection centers (BCCs), blood production centers (BPCs), blood distribution centers (BDCs), and demand points. A lot of effort is required to collect blood for transfusion (Elalouf et al, 2018); blood donation is free and a voluntary activity in most countries. The rate of blood donation varies across different countries; for example, only 5% of the people in the United States donate blood, of which 8% do it regularly and about 62% of them never visited BCC again (Zahiri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%